2012
DOI: 10.4103/0973-1075.100832
|View full text |Cite
|
Sign up to set email alerts
|

Study of nurses′ knowledge about palliative care: A quantitative cross-sectional survey

Abstract: Context:Studies have documented that nurses and other health care professionals are inadequately prepared to care for patients in palliative care. Several reasons have been identified including inadequacies in nursing education, absence of curriculum content related to pain management, and knowledge related to pain and palliative care.Aims:The objective of this paper was to assess the knowledge about palliative care amongst nursing professionals using the palliative care knowledge test (PCKT).Settings and Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…Our review of the literature and our own experiences led us to postulate that inpatient staff nurses may not be prepared to provide optimal care to end of life (EOL) and palliative care patients and their families (Chan and Webster, 2011; Patel, Gorawara-Bhat, Levine, and Shega, 2012; Prem, Karvannan, Kumar et al, 2012; Agustinus, Wai Chi Chan, 2013). Palliative care patients can continue to seek curative treatments while evaluating their goals and care needs.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the literature and our own experiences led us to postulate that inpatient staff nurses may not be prepared to provide optimal care to end of life (EOL) and palliative care patients and their families (Chan and Webster, 2011; Patel, Gorawara-Bhat, Levine, and Shega, 2012; Prem, Karvannan, Kumar et al, 2012; Agustinus, Wai Chi Chan, 2013). Palliative care patients can continue to seek curative treatments while evaluating their goals and care needs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there is a deficit of PC-related knowledge among health professionals (Prem et al, 2012). This raises the awareness for the need to improve the teaching of PC in undergraduate degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of incorporation of PC-related contents into the curricula of undergraduate degrees in the health area is a well-known fact (Al Qadire, 2014;WHO, 2015). The gaps identified in nursing degrees include topics such as management of pain and other symptoms, use of opiates and other specific medications, and management of side effects (Prem et al, 2012). In fact, there is a set of knowledge inherent to the proper treatment of people in PC that defies even the parameters established in evidence-based practice.…”
Section: Introductionmentioning
confidence: 99%
“…A study in India revealed that nurses and other health care professionals are inadequately prepared to provide pain management and palliative care for patients with chronic diseases as they only demonstrated a biomedical orientation to chronic pain rather than a behavioral one resulting in poor integration of palliative care [6].…”
Section: Health Workers' Knowledge On Use Of Integrated Palliative Camentioning
confidence: 99%